2014
DOI: 10.1002/ajpa.22614
|View full text |Cite
|
Sign up to set email alerts
|

Coastal, valley, and oasis interaction: Impact on the evolution of ancient populations in the South Central Andes

Abstract: The existing biocultural links are analyzed among ancient inhabitants of the Cochabamba valleys (Bolivia) from the Formative and Tiwanaku periods, coastal and inland Azapa region (Chile) from the Late Archaic to the Late periods, and the Atacama Desert oases (Chile) from the Formative period to the time of European contact. Craniometric information obtained from a sample of 565 individuals from different sites of the studied regions was evaluated using methods derived from quantitative genetics and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
3
0
4
Order By: Relevance
“…En general, por región el sexo masculino posee una menor divergencia entre grupos (2,7%) y la mayor tasa migratoria (aproximadamente 9 individuos por generación) con relación a la divergencia femenina (3,6%) y la tasa migratoria (aproximadamente 7 individuos por generación; Tabla 3). La existencia de flujo génico entre el NOA y NCH y, en general, en el AACS está de acuerdo con la evidencia etnográfica (Difrieri 1980) y con la información fenotípica y genética disponible en la actualidad (Cocilovo, Varela y Fuchs 2017; Cocilovo, Varela, Fuchs y Valdano 2017; Postillone et al 2017; Varela et al 1999, 2008, 2013, 2014).…”
Section: Discussionunclassified
“…En general, por región el sexo masculino posee una menor divergencia entre grupos (2,7%) y la mayor tasa migratoria (aproximadamente 9 individuos por generación) con relación a la divergencia femenina (3,6%) y la tasa migratoria (aproximadamente 7 individuos por generación; Tabla 3). La existencia de flujo génico entre el NOA y NCH y, en general, en el AACS está de acuerdo con la evidencia etnográfica (Difrieri 1980) y con la información fenotípica y genética disponible en la actualidad (Cocilovo, Varela y Fuchs 2017; Cocilovo, Varela, Fuchs y Valdano 2017; Postillone et al 2017; Varela et al 1999, 2008, 2013, 2014).…”
Section: Discussionunclassified
“…Sex and age estimations were based on morphology, fusion of the spheno‐occipital synchondrosis, cranial sutures, and dental eruption following the procedures outlined in Buikstra and Ubelaker (). Because the cultural practice of cranial vault modification (CVM) was prevalent throughout the prehistoric period in Chile, special care was taken to exclude any individuals with modified vaults, including those with minor modification on the frontal and lambdoidal region to avoid any effects that the modification could have on craniofacial assessments of biological affinity (Boston, Smith, Ubeda, Chandia, and Gonzalez, ; Rhode and Arriaza ; but see Varela et al, ). As such, the exclusion of intentional or nonintentional modifications hindered our ability to increase the skeletal sample in every region of Chile.…”
Section: Methodsmentioning
confidence: 99%
“…In Chile, fewer studies have assessed the Early skeletal series, and instead, much of the cranial research has addressed microevolution, the effects of climate, and regional variation of later‐period prehistoric populations. The majority of this work has utilized traditional, nonmetric, or 2D assessments (Marti and Rothhammer, ; Menéndez et al, ; Rothhammer, Quevedo, Cocilovo, and Llop, ; Rothhammer and Silva, ; Sutter, ; Torres‐Rouff, Knudson, & Hubbe, 2013; Varela, Cocilovo, Fuchs, and O'brien, ). Although researchers continue to debate the number of migratory waves responsible for peopling the continent through assessments of cranial variation (vonCramon‐Taubadel et al, 2017), genetic data have shown that there is biological continuity over a 9000‐year period in the Americas, with the initial dispersal having occurred along the Pacific coast (Chatters et al, ; Fagundes et al, ; Fehren‐Schmitz et al, ; Skoglund et al, ; Tamm et al, ; see also Raghavan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tiwanaku reached its apogee during the Middle Horizon period, around AD 700 [7], and began its decline by AD 900 [8]. Archaeological evidence suggests it expanded its sphere of influence by establishing permanent colonies in many surrounding territories [3,9] among which the Osmore-or Moquegua-Valley in southern Peru [10] and the Azapa Valley in northern Chile [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%